Transcatheter heart valve interventions for patients with rheumatic heart disease - Weich, Hellmuth; Herbst, Philip; Smit, Francis; Doubell, Anton (Frontiers in Cardiovascular Medicine, 2023)
Rheumatic heart disease [RHD] is the most prevalent cause of valvular heart disease in the world, outstripping degenerative aortic stenosis numbers fourfold. Despite this, global resources are firmly aimed at improving the management of degenerative disease. Reasons remain complex and include lack of resources, expertise, and overall access to valve interventions in developing nations, where RHD is most prevalent. Is it time to consider less invasive alternatives to conventional valve surgery? Several anatomical and pathological differences exist between degenerative and rheumatic valves, including percutaneous valve landing zones. These are poorly documented and may require dedicated solutions when considering percutaneous intervention. Percutaneous balloon mitral valvuloplasty (PBMV) is the treatment of choice for severe mitral stenosis (MS) but is reserved for patients with suitable valve anatomy without significant mitral regurgitation (MR), the commonest lesion in RHD. Valvuloplasty also rarely offers a durable solution for patients with rheumatic aortic stenosis (AS) or aortic regurgitation (AR). MR and AR pose unique challenges to successful transcatheter valve implantation as landing zone calcification, so central in docking transcatheter aortic valves in degenerative AS, is often lacking. Surgery in young RHD patients requires mechanical prostheses for durability but morbidity and mortality from both thrombotic complications and bleeding on Warfarin remains excessively high. Also, redo surgery rates are high for progression of aortic valve disease in patients with prior mitral valve replacement (MVR). Transcatheter treatments may offer a solution to anticoagulation problems and address reoperation in patients with prior MVR or failing ventricles, but would have to be tailored to the rheumatic environment. The high prevalence of MR and AR, lack of calcification and other unique anatomical challenges remain. Improvements in tissue durability, the development of novel synthetic valve leaflet materials, dedicated delivery systems and docking stations or anchoring systems to securely land the transcatheter devices, would all require attention. We review the epidemiology of RHD and discuss anatomical differences between rheumatic valves and other pathologies with a view to transcatheter solutions. The shortcomings of current RHD management, including current transcatheter treatments, will be discussed and finally we look at future developments in the field.